Rainha Santa Isabel. Fontes para o seu Estudo - Helena Costa Toipa (Documentos, 2020)
The veneration and worship of Queen Saint Elisabeth, in Portugal, started shortly after her death in 1336 and were registered in chronistic, hagiographic, biographical, notarial and other texts, that gathered abundant information about her life and miracles. Pedro Perpinhão, member of the Society of Jesus, who worked as a teacher, orator and researcher in Portugal between 1551 and 1561, wrote in Latin a biography about Queen Saint Elisabeth of Portugal, De Vita et Moribus Beatae Elisabethae Lusitaniae Reginae, that was the first in this language and the most complete work ever written. To compose it, he consulted all Portuguese medieval sources and used them exhaustively and impartially in order to be completely faithful to historical truth. This first Latin biography of Queen Saint' Elisabeth gathers all the knowledge of the time about her more than two centuries after her death.